Transcriptomic response to thermal and salinity stress in introduced and native sympatric Palaemon caridean shrimps. Issue 1 (December 2017) - Marie, Amandine; Smith, Steve; Green, Andy; Rico, Ciro; Lejeusne, Christophe
Abstract Organisms develop local adaptations to cope with spatially and temporally variable environments such as estuarine habitats, where abiotic parameters such as salinity and temperature fluctuate continuously. Studying the regulation of gene expression in a variable environment allows us to understand the underlying molecular mechanisms of these adaptations and the relative roles of the genetic and plastic response. The transcriptomes of the European nativePalaemon longirostris (PL) and the introducedP. macrodactylus (PM) shrimps are described and compared after an experiment simulating summer conditions in the Guadalquivir Estuary, Spain. Specimens, collected in the Guadalquivir Estuary, were maintained at a temperature and salinity of 20 °C and 5 ppt for the control, and 30 °C and 15 ppt for the stress treatment. A large amount of differential gene expression was observed: 16, 013 and 2, 594 for PL and PM respectively. Functionally annotated unigenes revealed some differences, with PL seemingly having to face stronger physiological stress than PM. Thus, PM seems to have greater resistance than PL under conditions of high temperature and salinity. These results constitute a step forward in the understanding of the underlying molecular mechanisms of genetic adaptation of native invertebrates, and alien taxa that have successfully invaded estuaries in temperate regions around the world.